Inhibition of the human neutrophil oxidative metabolism by Baccharis dracunculifolia DC (Asteraceae) is influenced by seasonality and the ratio of caffeic acid to other phenolic compounds - Figueiredo-Rinhel, Andréa S.G.; Kabeya, Luciana M.; Bueno, Paula C.P. [UNESP]; Jorge-Tiossi, Renata F.; Azzolini, Ana Elisa C.S.; Bastos, Jairo K.; Lucisano-Valim, Yara Maria (Elsevier, 2013)
Ethnopharmacological relevance: The great potential of phytotherapic drugs for treating and preventing inflammatory diseases mediated by increased neutrophil reactive oxygen species (ROS) generation has guided the search for new natural products with antioxidant and immunomodulatory properties. Baccharis dracunculifolia D.C. (Asteraceae), the main botanical source of Brazilian green propolis, is a native plant from Brazil widely used in folk medicine as anti-inflammatory. This study aims: (a) to determine the influence of seasonality on the chemical profile and biological activity of Baccharis dracunculifolia (Asteraceae) leaf extracts (BdE); (b) to analyze the correlation between the major compounds and the ability of BdE to modulate the superoxide anion and total ROS generation by human neutrophils. Materials and methods: The extracts were obtained from leaf samples collected monthly during one year. The superoxide anion and total ROS generation were assessed by the lucigenin (CL-luc)- and luminol (CL-lum)-enhanced chemiluminescence assays. Results: Seasonality influenced more the quantitative than the qualitative chemical profile of B. dracunculifolia, and affected its biological activity. The major compounds identified were caffeic acid, p-coumaric acid, aromadendrin-4′- methyl ether (AME), isosakuranetin and artepillin C. The IC50 values obtained for CL-lum and CL-luc inhibition by BdE ranged from 8.1-15.8 and 5.8-13.3 μg mL-1, respectively, and correlated positively with caffeic acid concentration. CL-luc inhibition correlated negatively with the concentration of artepillin C, AME, isosakuranetin and total flavonoids. The BdE sample from May/07 inhibited CL-lum and CL-luc the most strongly (IC 50=8.1±1.6 and 5.8±1.0 μg mL-1, respectively), and contained the highest ratio of caffeic acid to the other isolated compounds; so, this ratio could be employed as chemical marker for this biological activity of B. dracunculifolia. Conclusion: The ability of B. dracunculifolia to inhibit the neutrophil ROS generation depends more on the type and ratio of phenolic compounds and flavonoids than on their high absolute concentrations. Together, our results help select the most appropriate plant material for the production of phytotherapic drugs to be used in the treatment of inflammatory diseases mediated by increased neutrophil activation. © 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Antioxidant activity; Baccharis dracunculifolia; Flavonoids; Neutrophils; Phenolic compounds; Seasonality